FORECAST OF BENDING FATIGUE LIFE FOR GEARS CONSIDERING THE INFLUENCE OF RESIDUAL STRESS AND HARDNESS - ZHAO Pengbo; CHEN Yong; YOU Hui; ZHOU Xingyun; LI Guangxin; WU Yimin; LIU Xianghuan (Jixie qiangdu)
In order to study the influence of residual stress and hardness on bending fatigue performance of gear, the 20MnCrS5 steel gear with carburizing heat treatment was taken as the research object, and composite small diameter shot peening strengthening treatment was carried out to realize the gear with different hardness and residual stress states of the same material.Based on the maximum principal strain criterion, incorporating separate factors for residual stress influence and residual stress-hardness coupling influence were introduced respectively to establish the fatigue life prediction model.Through shot-peened gear bending fatigue tests, optimal values for both the residual stress influence coefficient and correction coefficient were determined.The two models’ accuracy for life prediction was contrasted, and the accuracy of these models was further verified through unshot peened gear bending fatigue test.The results show that considering only residual stress influence yielded an optimal value of 0.09 for the residual stress influence coefficient, the model achieving high life predictive accuracy.Whereas considering the effects of residual stresses and hardness, it requires a correction coefficient with an optimal value of 0.04, the model achieve even higher predictive accuracy.